Overdenture supported by richmond copings: A clinical report - Sonia Madaan Nanda; Tarun Nanda; Jagjit Singh; Rina Singh (Wolters Kluwer Medknow Publications, 2012)
The conventional modality of treatment of partial edentulousness with reduced number of teeth is to render them completely dentulous and provide them complete denture or an overdenture with support of few remaining teeth. The goal of maintenance of roots are to prevent alveolar bone resorption, provide better load transmission, maintain sensory feedback and achieve better stability of denture with emphasis on psychological aspect of not being completely edentulous. This clinical report aims at evaluation of tooth supported mandibular overdenture treatment with telescopic copings.